Interactive learning adventures: Learn coding through gamification - Ong, Zhan Wen (2024)

(untitled)
Coding through gamification introduces the concept of using game-like elements in the context of teaching coding skills. This approach aims to enhance the learning experience and engagement of learners in coding, which is a traditionally complex and technical subject. By incorporating elements such as challenges, rewards, and interactive scenarios inspired by games, coding education becomes more accessible, enjoyable, and effective. Furthermore, with the target subjects being children, chances of them being able to take an interest into coding through the usage of gamification will be more successful. Teaching coding through gamification for children will have benefits such as increased motivation, improved problem-solving skills, and the development of a growth mindset. It can also highlight how gamification encourages learners to explore coding concepts independently, fostering creativity and a deeper understanding of programming principles.